(untitled) (LSP International Journal, 2017)
This on-going study is carried out in order to identify the contents of incident reports obtained from an oil and gas contracting company. This is done through Interdiscursivity approach (Fairclough, 1992) by analyzing fifteen copies of summary of incident reports obtained from the company which was responsible in building turrets its international oil and gas clients. Incident report refers to a report produced when an accident or casualty happens at work. However due to legal constraints, the actual reports were not obtained. Instead, only summary of reports were obtained. Following that, interviews with engineers and supervisors were held in order to investigate further the generic resources (professional cultures and practices, Bhatia 2010) that influenced the production of the reports. However, only seven reports have been analyzed at the time of writing and data from the interview were not analyzed. Therefore, only findings from seven reports will be presented.